Methane oxidation linked to chlorite dismutation - Miller, Laurence G.; Baesman, Shaun M.; Carlström, Charlotte I.; Coates, John D.; Oremland, Ronald S. (Frontiers in Microbiology, 2014)
We examined the potential for CH4 oxidation to be coupled with oxygen derived from the dissimilatory reduction of perchlorate, chlorate or via chlorite (ClO2-) dismutation. Although dissimilatory reduction of ClO4- and ClO3- could be inferred from the accumulation of chloride ions either in spent media or in soil slurries prepared from exposed freshwater lake sediment, neither of these oxyanions evoked methane oxidation when added to either anaerobic mixed cultures or soil enriched in methanotrophs. In contrast, ClO2- amendment elicited such activity. Methane (0.2 kPa) was completely removed within several days from the headspace of cell suspensions of Dechloromonas agitata CKB incubated with either Methylococcus capsulatus Bath or Methylomicrobium album BG8 in the presence of 5 mM ClO2-. We also observed complete removal of 0.2 kPa CH4 in bottles containing soil enriched in methanotrophs when co-incubated with D. agitata CKB and 10 mM ClO2-. However, to be effective these experiments required physical separation of soil from D. agitata CKB to allow for the partitioning of O2 liberated from chlorite dismutation into the shared headspace. Although a link between ClO2- and CH4 consumption was established in soils and cultures, no upstream connection with either ClO4- or ClO3- was discerned. This result suggests that the release of O2 during enzymatic perchlorate reduction was negligible, and that the oxygen produced was unavailable to the aerobic methanotrophs.